HUBUNGAN POLA MAKAN DENGAN STATUS GIZI PADA BALITA USIA 1-4 TAHUN DI LINGKUNGAN II KELURAHAN NAMOGAJAH MEDAN TAHUN 2013 - Hamonangan Damanik (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2019)
Diet interpreted as setting the number and type of food eaten for someone to stay healthy. Nutritional status is an expression of a state of equilibrium in the form of a certain variable, or the embodiment of nutriture in the form of certain variables. Design research is descriptive that aims to determine the relationship of diet and nutritional status of children aged 1-4 years. Samples were whole population (total sampling) which is about 32 people. Data collected by kuesioer. The results of this study showed a frequency of 32 respondents with a good meal majority have good nutritional status is 21 people (65.62%). Frequency of 7 respondents who eat poorly majority experiencing poor nutritional status are 4 people (12.50%). Chi-Square test statistic values obtained were 4.93 and X²tabel X²hitung with degrees of freedom (df) 1 is 3.841, so it is stated that X²hitung (4.93)> X²tabel (3,841), which means that there is a significant relationship between the frequency of eating and nutritional status in infants aged 1-4. Of the 32 respondents with good portions majority have good nutritional status is 18 people (56.25%). Of the 11 respondents who are eating poorly majority experiencing good nutritional status are 6 people (18.75%). Chi-Square test statistic values obtained X²tabel with degrees of freedom (df) 1 is 3.841, so it is stated that X²hitung (3.73) <X²tabel (3,841), which means there is no significant relationship between eating and nutritional status. Of the 32 respondents with a good majority of the types of foods have good nutritional status is 17 people (53.12%). Of the 13 respondents that type of food is not good majority experienced a good nutritional status are 7 people (21.88%). Chi- Square test statistic values obtained X²tabel with degrees of freedom (df) 1 is 3.841, so it is stated that X²hitung (5.23)> X²tabel (3,841), which means that there is a significant relationship between the type of food with nutritional status of infants aged 1-4 year in Lingkungan II Kelurahan Namogajah. It is advisable for parents especially mothers to raise awareness of the importance of the application of a good diet to improve the nutritional status of children.